Pengaruh model pembelajaran pencapaian konsep ( concept attainment) terhadap hasil belajar siswa pada materi larutan elektrolit dan non elektrolit - Lumbantoruan, Jenti; Simson Tarigan (ARKA INSTITUTE, 2022)
This study aims to determine the learning outcomes of students of class X MIPA SMA N 1 Lintongnihuta who were taught using the concept attainment learning model and who were taught using conventional learning on electrolyte and non-electrolyte solution materials and to find out the significant influence of the application of the learning model concept attainment to improve student learning outcomes on electrolyte and non-electrolyte solutions. The population in this study were students of class X MIPA SMA N 1 Lintongnihuta, totaling 6 classes. The research sample was class X MIPA 3 as an experimental class which was taught using a concept attainment learning model and class X MIPA 5 as a control class which was taught using conventional learning. This study used a test instrument of 17 multiple choice questions. The results showed that the average experimental class student learning outcomes before and after the application of the concept attainment learning model were 44,58 and 78,83 respectively, and increased by 61%. The average learning outcomes of control class students before and after conventional learning were carried out were 42,33 and 70,52 respectively, and increased by 48%. Hypothesis testing was carried out with a one-party t test with the results of research on the concept attainment learning model, the results obtained were tcount(3.542) > ttable(1.996), then H0 was rejected and Ha was accepted, which means there is a significant effect on the use of the learning model on concept attainment on student learning outcomes on electrolyte and non-electrolyte solutions.